FORMATION OF SOCIAL CHARACTERISTICS OF CHILDREN OF PRESCHOOL AGE IN THE FAMILY - Djumaeva Sanobar Absaatovna; Kodirova Nilufar Maksudovna (American Journals, 2024)
This article discusses the role of the family institution in the socialization of the child. The article also analyzes the methods of raising children in the family. Proposals and recommendations regarding the mutual cooperation of the educational institution and the family in the social development of the child were considered.
Keywords: family, upbringing, socialization, development, cooperation, individualization, education, integration.